Interprofessional Collaboration in a New Model of Transitional Care for Families with Preterm Infants – The Health Care Professional’s Perspective - Schuetz Haemmerli N; von Gunten G; Khan J; Stoffel L; Humpl T; Cignacco E (Journal of Multidisciplinary Healthcare, 2021)
Natascha Schuetz Haemmerli,1,2 Geraldine von Gunten,1,2 Jeannine Khan,1 Liliane Stoffel,2 Tilman Humpl,2 Eva Cignacco1 1Department of Health Professions, Bern University of Applied Sciences, Bern, Switzerland; 2Inselspital, University Children’s Hospital, Neonatology, Bern, SwitzerlandCorrespondence: Natascha Schuetz HaemmerliBern University of Applied Sciences, Murtenstrasse 10, Bern, CH-3008, SwitzerlandTel +41 31 848 47 13Email natascha.schuetzhaemmerli@bfh.chBackground: Families with preterm infants find life after hospital discharge challenging and need tailored support to thrive. The “Transition to Home (TtH)”-model offers structured, individual support for families with preterm infants before and after hospital discharge. TtH improves parental mental health and competence, promotes child development and fosters interprofessional collaboration (IPC).Aim: Evaluate the TtH-models’ structure and implementation process and its associated interprofessional collaboration from the healthcare professional’s (HCP) perspective.Methods: This qualitative explorative study thematically analyzed four focus group interviews (n=28 HCP) and an open-ended questionnaire with general pediatricians (n=8).Results: The main themes of the thematic analysis were the benefits of the TtH-model, tailored parental support, the challenges of changing interprofessional collaboration, facilitators and barriers to successfully implementing the model, and feasibility and health economic limits. HCP acknowledge that continuous family-centered care led by an advanced practice nurse (APN) supports, strengthens, and relieves families with preterm infants in the transition from hospital to home. Families in complex situations benefit most. The TtH-model incorporates key aspects of integrated care like shared decision-making, considering family preferences, and defining the APN as the family’s main contact. HCP want network collaboration but found communication, cooperation, and reorganization challenging in the new IPC process. IPC challenges and involving many HCP in family care can create parental oversupply, negatively affect treatment outcomes, and raise health care costs.Conclusion: These challenges need to be addressed to ensure sustainable implementation of the model. The roles and tasks of HCP should be clearly distinguished from each other, and HCP must have time to learn this new form of IPC. Learning requires time, effective communication strategies, and leadership support. Political action is also required to implement new models of care, including regulating advanced practice roles and developing new financing models.Keywords: interprofessional collaboration, transition from hospital to home, new model of care, advanced practice nurse, preterm birth, qualitative research